Puyehue-Cordón Caulle eruption of 2011: tephra fall and initial forest responses in the Chilean Andes - Swanson,Frederick J (Universidad Austral de Chile, Facultad de Ciencias Forestales, 2016)
The 2011 eruption in the Puyehue-Cordón Caulle volcanic complex deposited up to 50 cm of tephra in a plume that intersected the crest of the Andes along Route 215, offering an excellent opportunity to study disturbance effects on native forests along a gradient of tephra depth. Our observations focused on short-term, species-level, tree mortality and sprouting and tephra fall effects on foliage and limb fall. More than 80 % of the thickest deposits were composed of a basal, pumice, gravel layer containing individual clasts up to 6 cm in length overlain by finer gravel and capped by several cm of sandy tephra. In a sample of four plots with tephra thickness ranging from 10 to 50 cm, we observed a wide range of tree mortality: about 8 % of stems living at the time of the eruption were killed by 10 cm of tephra fall and 54 % were killed by 50 cm. However, properties of the affected forest, such as species composition, foliage sprouting and retention (deciduous versus evergreen) characteristics, and tree size/age, strongly influenced survival. The sites with 35 and 50 cm thick deposits were dominated by the deciduous tree Nothofagus pumilio, which was leafless in the austral winter, season of the initial phase of the eruption. The evergreen tree N. dombeyi experienced much higher mortality. The low density of the falling pumice particles appeared to cause minimal abrasion of the canopy.